Improving High School Students’ English Speaking Skills Through the Use of Role Play - Ardi Nugroho; Magdalena Kartikasari Tandy Rerung; Rex Stardy; Jonathan Tanihardjo (Universitas Persada Indonesia YAI, 2026)
Among the various English language skills, speaking is considered particularly important. Nevertheless, English language teachers, particularly in Indonesia, often encounter difficulties in teaching students to speak English. Therefore, effective methods and strategies are needed to facilitate the teaching of English speaking skills, one of them is the use of role play. The English Study Program at Bunda Mulia University conducted a program at Fons Vitae 1 Senior High School in which the focus is on the use of role play to improve the students’ speaking skills. Various topics and situations were used such as asking for directions, asking about products and services, making hotel reservations, job interviews, etc. The findings reveal that through role play, the students were able to speak in English quite well in the various role play situations. The students also generally had a positive view regarding the use of role play to improve their speaking.